3D FEM simulation of chip breakage in metal cutting. Issue 1 (January 2016) - Buchkremer, S.; Klocke, F.; Veselovac, D.
Abstract In metal cutting, unbroken chips may scratch the machined surface and hinder an efficient chip removal. Despite its relevance, the established methodologies of tool/process design with regard to chip breakage are still dominated by expensive empirical approaches. Valid predictive modeling helps to reduce the experimental effort and safe costs. Chip breakage initiates with ductile material fracture on the chip free surface. The fracture strain is influenced by the temperature and stress state, which is defined by the stress triaxiality and Lode angle. An introduction of fracture models considering these combined impacts to the finite element (FE) simulation of chip breakage is not available. In this work, a new model of final ductile fracture is proposed, calibrated, and applied for the 3D FE simulation of chip breakage in turning processes of AISI 1045 (C45E+N). The calculation of the fracture strain considers the stress triaxiality, Lode angle, and temperature. A new non-iterative calibration procedure is proposed, which describes the relationships between the chip geometry at breakage and the thermomechanical state variables on the chip free surface. By implementing experimentally obtained chip geometries into this methodology, the combinations of strain, stress triaxiality, Lode angle, and temperature are determined under which ductile fracture was observed in the cutting tests. Finally, a regression analysis delivers all material constants. The fracture model is implemented into a FE-chip formation model. The predicted locations of fracture are compared to high-speed videos of turning experiments while the direction of crack propagation is validated by scanning electron microscopical images of experimental chips.